Communities of learned experience : epistolary medicine in the Renaissance - Siraisi, Nancy G. (Singleton Center books in premodern Europe., 2013)
"During the Renaissance, collections of letters both satisfied humanist enthusiasm for ancient literary forms and provided the flexibility of a format appropriate to many types of inquiry. The printed collections of medical letters by Giovanni Manardo of Ferrara and other physicians in early sixteenth-century Europe may thus be regarded as products of medical humanism. The letters of mid- and late sixteenth-century Italian and German physicians examined in Communities of Learned Experience by Nancy G. Siraisi also illustrate practices associated with the concepts of the Republic of Letters: open and relatively informal communication among a learned community and a liberal exchange of information and ideas. Additionally, such published medical correspondence may often have served to provide mutual reinforcement of professional reputation. Siraisi uses some of these collections to compare approaches to sharing medical knowledge across broad regions of Europe and within a city, with the goal of illuminating geographic differences as well as diversity within social, urban, courtly, and academic environments of medical learning and practice. The collections she has selected include essays on general medical topics addressed to colleagues or disciples, some advice for individual patients (usually written at the request of the patient's doctor), and a strong dose of controversy."--Project Muse